Pengaruh Model Pembelajaran Make A Match Terhadap Hasil Belajar Siswa Dalam Pembelajaran IPS Sekolah Dasar - Sri Mulyani; D. Wahyudin; Sofiahtun Ni'mah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Social studies learning is one of the learning that is applied at the elementary school level. Through social studies learning, social studies learning is guided, supported and assisted in order to become a quality human being. Therefore, social studies learning should be implemented properly. The purpose of this study was to determine the effect of Make A Match learning model on student outcomes in learning social studies elementary school. This research is included in quasi-experimental research with a design that is nonequivalent pretest-posttest control group design. The sample used was grade IV elementary school students as many as 20 students. This design divides into two groups, namely the experimental group and the control group. Based on the results of the study, there is a significant effect of using the Make A Match model by 20%. Thus stated, the Make A Match learning model has an influence in supporting students to understand and remember the subject matter. This can be seen from the average score before and after treatment. In addition, there is an increase in student learning outcomes known from the average N-Gain score of the experimental group which is 0.5075 with a moderate category. While the control group obtained an average N-Gain score of 0.2295 in the low category. The average N-Gain score of the experimental group was higher than the control group. So it can be stated that learning using the Make A Match model is better than conventional learning. Keywords: Make A Match learning model; social studies learning; learning outcomes.